2012
DOI: 10.1002/ajmg.a.35535
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Disabilities Network (LeaDNet): Using neurofibromatosis type 1 (NF1) as a paradigm for translational research

Abstract: Learning disabilities and other cognitive disorders represent one of the most important unmet medical needs and a significant source of lifelong disability. To accelerate progress in this area, an international consortium of researchers and clinicians, the Learning Disabilities Network (LeaDNet), was established in 2006. Initially, LeaDNet focused on neurofibromatosis type 1 (NF1), a common single gene disorder with a frequency of 1:3,000. Although NF1 is best recognized as an inherited tumor predisposition sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 58 publications
0
31
0
1
Order By: Relevance
“…One common feature of the RASopathies is some degree of neurocognitive involvement, which is an attractive target for treatment (1). The first randomized, placebo-controlled, double-blind clinical trial examined the effect of a 12-week simvastatin treatment on cognitive function in children with NF1 (30).…”
Section: Considerations For Systemic Treatment Of Germline Effectsmentioning
confidence: 99%
“…One common feature of the RASopathies is some degree of neurocognitive involvement, which is an attractive target for treatment (1). The first randomized, placebo-controlled, double-blind clinical trial examined the effect of a 12-week simvastatin treatment on cognitive function in children with NF1 (30).…”
Section: Considerations For Systemic Treatment Of Germline Effectsmentioning
confidence: 99%
“…However, results of initial trials using simvastatin did not support short-term efficacy in providing clear functional benefits (Krab et al 2008;van der Vaart et al 2013). NF1 treatment trials to evaluate statin drugs using larger, more carefully selected samples are ongoing (Acosta et al 2012). Importantly, there is now evidence to demonstrate that drugs targeting the same mechanism can be effective in ameliorating cognitive deficits in mouse models of NS (Lee et al 2014), suggesting a potential avenue for future therapeutic exploration.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Some researchers have advised that to optimally translate scientific advances into clinical interventions, a collaborative framework to include neuroscientists and clinicians from diverse institutions must be developed (Acosta et al 2012). The complexity of the challenges facing evaluation of clinical therapies (e.g., measurement considerations, recruitment of sufficient numbers of participants) will require interdisciplinary contributions and multi-site partnerships.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Clinical studies examining cognitive problems in NF1 have revealed a left shift in average IQ, ranging from low-to-normal IQs, with specific learning deficits observed in 30–70% of children [1, 14, 15]. Additionally, children with NF1 exhibit poor performance on tasks of reading, spelling and mathematics, impaired expressive and receptive language skills, deficits in visuospatial and visuoperceptual skills, and defects in executive function (planning and concept formation) [1, 16, 17]. While less common, there is also an increased incidence of autistic spectrum disorder in children with NF1 [18].…”
Section: Clinical Features Of Nf1mentioning
confidence: 99%